Precise Onboard Orbit Determination for LEO Satellites with Real-Time Orbit and Clock Corrections - Hauschild, Andre; Tegedor, Javier; Montenbruck, Oliver; Visser, Hans; Markgraf, Markus (ION GNSS+, The International Technical Meeting of the Satellite Division of The Institute of Navigation, Proceedings of the 29th International Technical Meeting of The Satellite Division of the Institute of Navigation (ION GNSS+ 2016), 2016)
Precise Point Positing (PPP) with real-time orbit and clock correction streams has become an established technique over the last decade for land, air and sea applications. The use of real-time corrections for precise positioning has not extended into orbit yet, although a number of low-Earth orbit (LEO) satellite missions have a demand for precise orbit determination (POD). Future satellites with altimeter and radio-occultation payloads may require real-time POD to enable onboard processing of science data for forecasting or nowcasting of meteorology data, open-loop instrument operations of radar payloads, or quick-look onboard science data generation. Also, precise real-time orbit information may be utilized for constellation maintenance of satellite formations. A POD accuracy of a few decimeters or better with precise GPS real-time corrections has repeatedly been demonstrated in the past. For these studies it was assumed that the corrections are continuously available. This is, however, not guaranteed to be the case in a realistic on-orbit scenario, in which the corrections are disseminated via a network of geostationary (GEO) satellites to the LEO satellite. The data link to the GEO constellation may not be available over the polar regions, thus outdated corrections must be used until up-to-date data is received again. These correction data gaps will have an adverse effect on the POD accuracy, especially since the satellite visibility is typically also reduced as well over the North and South pole. To assess the effect of outdated correction data on onboard POD, a Kalman-filter-based navigation algorithm has been used to process real-world GPS observations of a representative LEO satellite mission together with corrections based on real-time orbit and clock products from Fugro. Data gaps of different length have been simulated, during which the corrections must be extrapolated. The magnitude of orbit and clock extrapolation errors is assessed. Clock extrapolation errors are evaluated depending on the ...